Synthesis and evaluation of the complex-forming ability of hydroxypyranones and hydroxypyridinones with Ni (II) as possible inhibitors for urease enzyme in Helicobacter pylori - Abbasali Palizban; Lotfollah Saghaie (Wolters Kluwer Medknow Publications, 2016)
The complex-forming ability of 2-methyl-3-hydroxypyran-4-one ( 1a ), 2-ethyl-3-hydroxypyran-4-one ( 1b ), 1,2-dimethyl-3-hydroxypyridin-4-one ( 4a ) and 1-ethyl-2-methyl-3- hydroxypyridin-4-one ( 4b ) with nickel(Ni(II)) were characterized by infrared, ultraviolet, proton nuclear magnetic resonance spectroscopy and melting point. The mole-ratio of nickel:ligands was analyzed by atomic-absorption-spectrometry. The partition-coefficients (K OW ) of the compounds were also determined. The binding of ligands with Ni(II) are through deprotonated hydroxyl group (-O - , disapeared at 3259 cm -1 and ioan-pairs of carbonyl group (=CO . , shifted from 1650 to 1510-1515 cm -1 . The characterization of complex geometry for bis-(2-methyl-3-hydroxypyranonato)Ni(II) ( 5a ) and bis-(2-ethyl-3-hydroxypyranonato)Ni(II) ( 5b ) predicted to be square-planer while for bis-(1,2-dimethyl-3-hydroxypyridinonato)Ni(II) ( 5c ) and bis-(1-ethyl-2-methyl-3-hydroxypyridinonato)Ni(II) ( 5d ) distorted to tetrahedral-geometry. Inhibitors of Helicobacter pylori urease are nickel chelators. The compounds 1a , 4a and 4b are likely suitable ligands with complex forming-ability to make complexes of 5a , 5c and 5d with nickel. The K OW values show the compound 5c with low partition-coefficient is more suitable ligand with lower penetration from GI lumen. Future studies demand to find out the biological activity of developed compounds on H. pylori.